To find the length of the other leg of a right triangle when one leg and the hypotenuse are known, we can use the Pythagorean theorem, which states:
\[ a^2 + b^2 = c^2 \]
where \( a \) and \( b \) are the legs of the triangle, and \( c \) is the hypotenuse.
Given:
- One leg \( a = 6 \) ft
- Hypotenuse \( c = 12 \) ft
We need to find the length of the other leg \( b \).
Using the Pythagorean theorem:
\[ 6^2 + b^2 = 12^2 \]
Calculating the squares:
\[ 36 + b^2 = 144 \]
Now, we isolate \( b^2 \):
\[ b^2 = 144 - 36 \] \[ b^2 = 108 \]
Next, we take the square root of both sides to find \( b \):
\[ b = \sqrt{108} \]
Now we can simplify \( \sqrt{108} \):
\[ \sqrt{108} = \sqrt{36 \times 3} = \sqrt{36} \times \sqrt{3} = 6\sqrt{3} \]
Next, we can approximate \( \sqrt{3} \approx 1.732 \):
\[ b \approx 6 \times 1.732 \approx 10.392 \]
Rounding to the nearest tenth:
\[ b \approx 10.4 \]
So, the length of the other leg is approximately 10.4 ft.